Definitive LC-MS/MS Drug Monitoring Impacts Substance-use Treatment Planning and Patient Outcomes: A Brief Report. Issue 6 (November 2016) - Rzetelny, Adam; Zeller, Barbara; Miller, Nicholas; Kirsh, Kenneth L.; Passik, Steven D.
Abstract : Clinical drug monitoring has an increasingly important role in the treatment of substance use disorders. Through semistructured interviews, we asked substance-use counselors about the clinical impact of drug tests on patients' treatment planning and outcomes. This study was conducted around the time of a facility-wide switch to a laboratory utilizing definitive liquid chromatography with tandem mass spectrometry from a laboratory that had utilized the less-sensitive, presumptive immunoassay-based drug-testing methodology. Twelve counselors volunteered to be interviewed, and each counselor chose 2 patients to discuss. Counselors reported that the facility-wide switch to definitive drug testing revealed some patients with newly identified relapses and substance use. They also reported that, as a result of the new information provided by definitive liquid chromatography with tandem mass spectrometry monitoring, 75% of the patients they discussed had a change made to their treatment plan, 79% were provided enhanced education, and 63% had an increase in their treatment intensity. Counselors also reported that 58% of these patients reduced their illicit drug and nonmedical prescription medication use as a result of treatment changes associated with the newly implemented definitive testing. Improvements in therapeutic relationships and honesty were also reported. These preliminary data are consistent with previous data and guidelines, suggesting that the results of definitive drug monitoring inform clinical decision-making and can help clinicians enhance treatment outcomes.